2004
DOI: 10.1108/09544780410532954
|View full text |Cite
|
Sign up to set email alerts
|

Integrating corporate social responsibility (CSR) into ISO management systems – in search of a feasible CSR management system framework

Abstract: Following the growing interest in corporate governance and corporate social responsibility (CSR), the International Organization for Standardization (ISO) Committee on Consumer Policy (ISO/COPOLCO) opened the discussion about the feasibility of CSR management system standard. In this paper, we investigate the underlying issues that shape the development of CSR standard. Based on our case study research, we provide a framework for organisations to establish, manage, improve and document a CSR management system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 26 publications
0
93
0
3
Order By: Relevance
“…The need for further research on the integration of corporate sustainability approaches with core business processes has been emphasized (Asif et al, 2011). In addition, scholars have often suggested the importance of such approaches being implemented into every level of an organization if they are to have a meaningful impact (Castka et al, 2004;Shahin and Zairi, 2007;Zadek, 2007). Second, the reviewed articles concluded that an IMS is beneficial for practitioners based on the commonalities found in the QMS and EMS standards.…”
Section: Discussionmentioning
confidence: 99%
“…The need for further research on the integration of corporate sustainability approaches with core business processes has been emphasized (Asif et al, 2011). In addition, scholars have often suggested the importance of such approaches being implemented into every level of an organization if they are to have a meaningful impact (Castka et al, 2004;Shahin and Zairi, 2007;Zadek, 2007). Second, the reviewed articles concluded that an IMS is beneficial for practitioners based on the commonalities found in the QMS and EMS standards.…”
Section: Discussionmentioning
confidence: 99%
“…The process of implementing CSR in core business processes, which is denoted in the literature for achieving effective long-term CSR performance (e.g., Accenture 2010; Castka et al 2004;Jamali 2008), is often managed by a select group of people (or sometimes even an individual); the CSR professional(s). These professionals bear the responsibility of effectively implementing CSR within the company.…”
Section: Introductionmentioning
confidence: 99%
“…SA8000 is strongly linked to corporate social responsibility. Academics and scholars used this standard to define a management system framework (Castka et al, 2004). Others consider that SA8000 represents a CSR initiative that can improve business reputation (Fombrun, 2005).…”
Section: Research Objectives and Methodologymentioning
confidence: 99%